Long-term Outcomes of Kidney Transplantation in Fabry Disease. Issue 11 (November 2018) - Ersözlü, Sara; Desnick, Robert J.; Huynh-Do, Uyen; Canaan-Kühl, Sima; Barbey, Frédéric; Genitsch, Vera; Mueller, Thomas F.; Cheetham, Marcus; Flammer, Andreas J.; Schaub, Stefan; Nowak, Albina
Abstract : Background: Fabry disease (FD) is a rare X-linked lysosomal storage disorder caused by mutations in the α-galactosidase A gene that obliterate or markedly reduce α-galactosidase A activity. This results in the systemic accumulation of its glycosphingolipid substrates in body fluids and organs, including the kidney. Fabry nephropathy can lead to end-stage renal disease requiring kidney transplantation. Little is known about its long-term outcomes and the overall patient survival after kidney transplantation. Methods: Here, we report 17 Fabry patients (15 male and 2 female subjects) who received kidney transplants and their long-term treatment and follow-up at 4 specialized Fabry centers. Results: The posttransplant follow-up ranged to 25 years, with a median of 11.5 (range, 0.8-25.5] years. Graft survival was similar, and death-censored graft survival was superior to matched controls. Fabry patients died with functioning kidneys, mostly from cardiac causes. In 2 male subjects 14 and 23 years posttransplant, the grafts had a few typical FD lamellar inclusions, presumably originating from invading host macrophages and vascular endothelial cells. Conclusions: We conclude that kidney transplantation has an excellent long-term outcome in FD. Abstract : This retrospective cohort study suggests that patients with chronic kidney disease due to Fabry disease who receive a kidney transplant and enzyme replacement therapy show long-term patient and graft survival that are at least comparable to matched controls.